Cyclopropyl Group: An Excited‐State Aromaticity Indicator?. Issue 55 (1st September 2017) - Ayub, Rabia; Papadakis, Raffaello; Jorner, Kjell; Zietz, Burkhard; Ottosson, Henrik
Abstract: The cyclopropyl (cPr) group, which is a well‐known probe for detecting radical character at atoms to which it is connected, is tested as an indicator for aromaticity in the first ππ* triplet and singlet excited states (T1 and S1 ). Baird's rule says that the π‐electron counts for aromaticity and antiaromaticity in the T1 and S1 states are opposite to Hückel's rule in the ground state (S0 ). Our hypothesis is that the cPr group, as a result of Baird's rule, will remain closed when attached to an excited‐state aromatic ring, enabling it to be used as an indicator to distinguish excited‐state aromatic rings from excited‐state antiaromatic and nonaromatic rings. Quantum chemical calculations and photoreactivity experiments support our hypothesis; calculated aromaticity indices reveal that openings of cPr substituents on [4 n ]annulenes ruin the excited‐state aromaticity in energetically unfavorable processes. Yet, polycyclic compounds influenced by excited‐state aromaticity (e.g., biphenylene), as well as 4 n π‐electron heterocycles with two or more heteroatoms represent limitations. Abstract : So exciting ! The cyclopropyl (cPr) group, which is a known probe for detecting radical character at atoms to which it is connected, was tested as an indicator for aromaticity in the first ππ* triplet and singlet excited states (T1 and S1 ; see scheme). Our hypothesis is that the cPr group, as a result of Baird's rule, will remain closed when attached to an excited state aromatic ring, enabling it to be used as an indicator to distinguish excited‐state aromatic rings from excited‐state antiaromatic and nonaromatic rings.